IMPLEMENTASI PERATURAN WALIKOTA SAMARINDA NOMOR 23 TAHUN 2010 TENTANG PENETAPAN LINTASAN ANGKUTAN BARANG DI WILAYAH KOTA SAMARINDA TERHADAP PETI KEMAS - Rabia Dewi Safitri (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT        The container transportation sector seems to have a tight level of competition, given the large number of private freight companies and there are not many obstacles to entering this sector and there are many service providers.        Transportation in people's lives is a very important role, because by transporting almost all economic activities and community activities, it can generally run smoothly. The role of transportation in the economic sector as from the economic activities themselves.         One form of implementation of the Samarinda Mayor Regulation Number 23 of 2010 concerning the Determination of Goods Transport Trajectories in the City of Samarinda Area is a Prohibition against every driver of freight transporting between 06:00 to 18:00 in the City of Samarinda enclosed in PERWALI Samarinda No. 23 of 2010.         The rules for limiting the trajectory of freight vehicles which are grouped with the class of road and the heaviest axle load (MST) must be obeyed by service users and drivers of vehicles because the roads in the area of Samarinda City are not intended for freight vehicles, especially the type of container trucks that are overloaded . Keywords: PERWALI Samarinda No. 23 of 2010, Container